Reality and Paternity in the Cinema of the Dardennes - Guanzini, Isabella (Journal for religion, film and media, 2016)
The Dardennes’ filmic production aims at restoring the missing link between human beings and the world that have been progressively undermined during the ultimate development of late-capitalist society. This contribution deals with their search for a new contact with reality and a concrete belief in the world, focusing on the theme of body and paternity, in the epoch of their evaporation. In order to rethink the paternal function in a post-political and post-ideological age, however, the Dardennes have had to radically come to terms with its ambiguity and oscillation between abandon and adoption, self-preservation and transmission, forgiveness and revenge. With regard to this ambivalence, this contribution focuses on The Promise and The Son, which represent significant descriptions of what (the body of) a father is capable of, suggesting, at the same time, interruption and filiation as possible experiences for a new beginning.